Statement by the Managing Director on the Independent Evaluation Office Report on Self-Evaluation at the IMF : An IEO Assessment. (Policy Papers; Policy Paper, 2015)
The thrust of the report's recommendations to strengthen the institutional framework for self-evaluation, adapt it over time to changing circumstances, and better disseminate lessons from self-evaluation are well taken. I believe, however, that there is considerable scope to address these recommendations by refining and building on existing processes and initiatives already underway rather than by introducing substantial new architecture. I see limited value added relative to the costs in following through with the report's two other key recommendations; namely, to conduct self-assessment for every IMF-supported program and to set out plans ex ante to self-evaluate every policy and thematic review.